Inheritance of resistance to common bacterial blight in common bean - Chataika, Bartholomew Y.E.; Bokosi, J.M.; Chirwa, R.M. (African Crop Science Society, 2011)
The common bean (Phaseolus vulgaris L.) is an important grain legume crop in Malawi where it is grown by small holder farmers for food as well as for sale. Among the many diseases that limit crop productivity is the common bacterial blight caused by Xanthomonas axonopodis pv phaseoli (Xap). Effective breeding for resistance to Xap requires understanding of the model of inheritance for resistance. A study to determine the inheritance of resistance to Xap in common bean was carried out in Malawi. Two established bean varieties originating from local landraces in Malawi (Chimbamba and Nasaka), plus one line (RC 15) from the breeding programme at Bunda College of Agriculture, were used as recipient (susceptible) parents; while Vax 6 from CIAT was the donor (resistant) parent. The progenies were advanced to F2 generations in greenhouses. The F2 populations were evaluated for resistance to Xap. The results showed that one recipient parent, Chimbamba, which is supposedly homogeneous, behaved like a segregating population and, therefore, modified the phenotypic ratios of the progenies. A Chi-square test using data generated from populations resulting from the three recipient parents showed that the inheritance of resistance to Xap was controlled by two major genes with possible minor genes involvement. The same was true when a Chi-square test was used to analyse the pooled data across populations generated from the three recipient parents (Chimbamba, Nasaka and RC 15), suggesting that inheritance of resistance to Xap was controlled by two major genes